Pathological Changes due to Copper Toxication in TwoSheep - Eroksuz, Yesari; İncili, Canan Akdeniz; Karabulut, Burak; Yılmaz, İsmet; Yerlikaya, Zeynep; Eröksüz, Hatice (My University, 2021)
Copper intoxication was reported in two animals from a herd of 160 grazing Akkaraman sheep.Gross findings included marked icterus, hemoglobinuric nephrosis and enhanced hepatic lobularpattern. Histopathological examination showed multifocal degenarative and necrotic changes inliver and kidney. Immunohistochemically; rhodanine-positive cytoplasmic staining was detectedmultifocally in hepatocytes and tubular epithelial cells. Hepatic and renal copper concentration was244.24 mg/1000 g and 70.35 mg/1000 g in wet tissues. Overall, data showed the presence ofapost-hemolytic phase of disease, in which renal damage is associated with hemoglobinuria.
Keywords: Patoloji; Veterinerlik